Farmers' Perceptions and The Impact of Agricultural Extension on Rice Productivity in Ciparay Sub-District, Bandung District - Anne Charina; Dinna Charisma; Rani Andriani BK (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Agricultural extension officers are agents of change who play a vital role in transferring technology and knowledge to improve farmers practices. However, the failure rate of traditional extension activities remains quite high in developing countries such as Indonesia. This study examines rice farmers’ perceptions of extension officers’ performance and the impact of extension services on rice productivity in Ciparay District, Bandung Regency. A quantitative approach was used, with data collected through questionnaires from 80 rice farmers (40 active participants in the extension program and 40 non-participants). Descriptive statistics and Propensity Score Matching (PSM) were applied. Results show that farmers’ perceptions of extension officers’performance are moderate in responsiveness, responsibility, accountability, and service quality. Participation in extension programs positively impacted rice productivity, with participating farmers achieving 8.12 tons/ha more than non-participants. To enhance effectiveness, the local government should ensure a balanced ratio of extension officers to farmers, particularly in high-density farming villages. Capacity-building programs should be tailored to Ciparay’s agroecological conditions, focusing on water management, adoption of locally suitable high-yield varieties, and integrated pest management. Extension activities should be conducted regularly, aligned with planting seasons, and employ participatory methods such as field schools for hands-on learning. Additionally, improving meeting facilities, providing demonstration tools, and expanding access to digital agricultural information are crucial to strengthening extension services and sustaining productivity gains in Ciparay District.